(untitled) (Revista de Turismo: Patrimônios, Territórios descoloniais e Trabalho, 2025)
Work in tourism has characteristics, such as seasonality, which favors the search for informal workers. The objective of this study was to investigate the working conditions of workers without employment contracts in the food sector (waiters/waitresses) in Diamantina/MG. Interviews were conducted with waiters/waitresses who work informally in the municipality. The main results regarding: contractual and legal conditions indicate precarious conditions regarding payment of overtime and service fees, minimum break time, hours worked and variable remuneration; physical and material conditions indicate a perception of a safe environment, but with divergences regarding the provision of PPE and deviations from function; regarding the processes and characteristics of the activities, the lack of investment in the qualification of workers and possibilities for growth in the job stood out; and regarding the socio-managerial environment, the pressure and demands stood out, with a great burden of responsibilities without proper training. Finally, reflections were made about the interconnections between decent work and sustainable tourism.